Exploratory study of the acute and mid-term effects of using a novel dynamic meeting environment (Aeris®) on cognitive performance and neurophysiological responses - Ammar, Achraf; Boujelbane, Mohamed Ali; Simak, Marvin Leonard; Fraile-Fuente, Irene; Trabelsi, Khaled; Bouaziz, Bassem; Rizzi, Nikolas; Schöllhorn, Wolfgang I. (Frontiers in Human Neuroscience, 2023)
This study aims to assess the acute and mid-term effects of the dynamic aeris®meeting-environment on brain activity, cognitive performance, heart rate variability (HRV), sleepiness, mental workload (EEG-MWI), as well as local experienced discomfort (LED) in healthy adults.Twenty-four healthy adults (16 females, age: 25.2±3.1 years old) were randomly assigned to either the control (i.e., conventional meeting environment, CG) or experimental (Aeris® dynamic meetingenvironment, DG) group with a 1:1 allocation. Participants reported to the laboratory on two test sessions separated by a two-week intervention period (5 meetings of 90 minutes each week).Spontaneous resting EEG and HRV activities, as well as attentional (D2-R test) and vigilance (PVT) cognitive performances, sleepiness perceptions, and EEG-MWI, were recorded at the beginning of each test session and immediately following the 90-min meeting. The LED was measured pre-and post-intervention. The changes (Δ) from preto post-90 min meeting and from pre-to postintervention were computed to further examine the acute and mid-term effects,respectively. Compared to the CG, the DG showed higher Δ (pre-post 90min-meeting) in fronto-central beta (p=0.016, d=1.10) and gamma (p=0.019, d=0.94) frequencies at postintervention. From pre-to post-intervention, only the DG group showed a significant increase in fronto-central gamma response (Δ) to the meeting session (p=0.04,d=1.08). The acute use of the Aeris®-meeting-environment during the 90-min meeting session seems to be supportive for (i) maintaining vigilance performance, as evidenced by the significant increase in N-lapses from pre-to post-90min session only in the CG (p=0.04, d=0.99, Δ= 2.5±3 lapses), and (ii) improving alertness, as evidenced by the lower sleepiness score (p=0.05, d=-0.84) in DG compared to CG. The mid-term use of such an environment showed to blind the higher baseline values of EEG-MWI recorded in DG compared to CG (p=0.01, d=1.05) and may prevent lower-back discomfort (i.e., a significant increase only in CG,p=0.05,d=0.78), suggesting a less mentally and physically exhausting meeting in this environment. There were no acute and/or mid-term effects of the dynamic meeting environment on any of the HRV parameters.These findings are of relevance in the field of neuroergonomics, as they give preliminary support to the advantages of meeting in a dynamic office compared to a static office environment.